PARAMETER GENETIK DAN ANALISIS HUBUNGAN ANTAR SIFAT PADA GENERASI F2 PADI HASIL PERSILANGAN INPARI 31 X BASMATI DELTA 9 - Agus Riyanto; Dyah Susanti; Totok Agung Dwi Haryanto (Jurnal Penelitian Pertanian Terapan, 2023)
One of the goals of Indonesia's rice improvement program is to develop high-yielding varieties with long and slender rice grains. This study aimed to estimate the genetic parameters affecting gene action, amount of gene action, number of gene control, magnitude of genetic variability, heritability, genetic advance, and correlations between yield components and yield of Inpari 31 x Basmati Delta 9 in the F2 generation. The experiment was carried out at an experimental farm at the Faculty of Agriculture, Jenderal Soedirman University, Purwokerto, Central Java, Indonesia. The genetic material used was seed from an F2 population crossed between Inpari 31 and Basmati Delta 9 with the two parental genotypes. Estimates of skewness, kurtosis, genetic variability, heritability, genetic advance, correlations between traits and path analysis were calculated for yield and yield component traits. Results show that additive and complementary epistatic action control yield-related and yield traits. Yield-related trait components and yield are controlled by a monogenic or polygenic genes, depending on the observed trait. Wide genetic variability, high broad sense heritability and high genetic advance were found in the number of productive tillers per hill and grain weight per panicle.  These traits show a significant positive correlation and have a direct effect on the yield; therefore, they can be used as traits in the selection to produce high-yielding rice, with long rice sizes and slender shapes.   Keywords: F2 population; genetic parameters; interrelationship among traits; rice